The severity of plastic shrinkage cracking in concrete: a new model. Issue 6 (8th March 2021) - Sayahi, Faez; Emborg, Mats; Hedlund, Hans; Cwirzen, Andrzej; Stelmarczyk, Marcin
Abstract : Plastic shrinkage cracking in concrete is mainly a physical process, in which chemical reactions between cement and water do not play a decisive role. It is commonly believed that rapid and excessive moisture loss due to evaporation is the primary cause of the phenomenon. This paper presents a new model to estimate the severity of plastic shrinkage cracking, based on the initial setting time and the amount of water evaporating from within the concrete bulk. A number of experiments were performed under controlled ambient conditions, during which the water/cement ratio, cement type and dosage of superplasticiser were altered. The results, alongside those reported by other researchers, were utilised to check the validity of the proposed model. According to the outcomes, the model could predict the cracking severity of the tested concretes with good precision.